Penerapan Komunikasi Penyuluhan Pertanian Milenial pada Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) di Desa Betet Kabupaten Nganjuk Jawa Timur - Sekar Renaningtyas; Puji Hariyanti (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
P4S is an agricultural extension agency established, owned, and managed by independent farmers. This study aims to analyze the communication model carried out by P4S as an extension agent in conducting counseling for the Millennial Farmer program carried out in Betet Village, Ngroggot District, Nganjuk Regency. The method used is a field qualitative method. The results showed that there were two phases in the extension of millennial farmers. In the pre-extension until the extension, the communication model used was linear so that in the pre-extension the models applied were unidirectional SMCR and two-way SMCR. After the extension, the communication model used is the network communication model and the forum media communication model.Keywords: Communication models, Millennial Farmers, Empowerment Communication